2023
DOI: 10.1007/s11060-023-04362-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment benefit in patients aged 80 years or older with biopsy-proven and non-resected glioblastoma is dependent on MGMT promoter methylation status

Abstract: Purpose Glioblastoma is associated with especially poor outcome in the elderly. It is unclear if patients aged ≥80 years benefit from tumor-specific therapy as opposed to receiving best supportive care (BSC) only. Methods Patients with IDH-wildtype glioblastoma (WHO 2021), aged ≥80 years, and diagnosed by biopsy between 2010 and 2022 were included. Patient characteristics and clinical parameters were assessed. Uni- and multivariate analyses were performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The benefits of PCV in oligodendroglioma, for example, are accrued mostly by patients with IDH-mutant and 1p/19q-codeleted tumors, and the benefits of PCV over radiotherapy are limited to IDH-mutant disease ( 136 , 159 ). The benefits of alkylating chemotherapy in elderly patients with newly diagnosed glioblastoma seem to be limited to patients with MGMT promotor methylation ( 113 ). These and similar findings have motivated the latest revision of the WHO glioma classification, which incorporates molecular changes that are clinicopathologically useful (at the cost of, as mentioned before, limiting “backwards compatibility” of study data) ( 7 , 86 , 198 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of PCV in oligodendroglioma, for example, are accrued mostly by patients with IDH-mutant and 1p/19q-codeleted tumors, and the benefits of PCV over radiotherapy are limited to IDH-mutant disease ( 136 , 159 ). The benefits of alkylating chemotherapy in elderly patients with newly diagnosed glioblastoma seem to be limited to patients with MGMT promotor methylation ( 113 ). These and similar findings have motivated the latest revision of the WHO glioma classification, which incorporates molecular changes that are clinicopathologically useful (at the cost of, as mentioned before, limiting “backwards compatibility” of study data) ( 7 , 86 , 198 ).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value is especially valuable in elderly and/or frail patients, in whom the MGMT promoter methylation status should always be assessed before deciding on therapy, as patients without methylated tumors may benefit to a much smaller extent from tumor-specific treatment and chemotherapy ( 112 ). For example, in a cohort of patients aged ≥80 years with IDH-wildtype glioblastoma, tumor-specific therapy conferred a median OS benefit of 2.1 months versus best supportive care (BSC), but only in patients with MGMT promoter methylation (median benefit of 3.6 months) while no benefit was observed in patients without MGMT promoter methylation ( 113 ). These and similar data strongly suggested that therapy be initiated dependent on MGMT promoter methylation status, which is already reflected in some treatment guidelines ( Table 2 ).…”
Section: Treating Gliomamentioning
confidence: 99%
“…Here, we emphasize the preoperative mean value of the KPI that was >70% even in both groups. Indeed, this KPI is associated with a good prognosis in general [ 3 ] and especially in combination with GTR [ 3 , 14 , 44 ]. Interestingly, despite the older age, the elderly group in our cohort proved to be fit overall as their median CCI was 3.23 and their preoperative KPI was 78.84 ± 14.9%.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the median survival after standard-of-care treatment is about ~18 months with survival after progression at 6–8 months [ 1 ]. Several predictors regarding the prognosis of glioma, such as initial clinical condition, age of the patient, extent of resection, molecular characteristics like mutation of the isocitrate-dehydrogenase 1 (IDH1) gene, and methylation of the O6-methylguanin-DNA-methyltransferase (MGMT) promotor are already described [ 2 , 3 , 4 , 5 , 6 ], but their significance regarding different age groups is not sufficiently investigated [ 2 , 7 , 8 ]. In particular, no clear indication exists for elderly glioblastoma patients ≥ 65 years, as no standard of care for the treatment of the elderly with glioblastoma (GB) has been established so far [ 9 , 10 , 11 ], although the incidence of GB in people over 65 years is more than twice as high as in younger people [ 12 ], it has a peak in patients aged from 75–84 years, and the population will be constantly increasing [ 13 ].…”
Section: Introductionmentioning
confidence: 99%